2010
DOI: 10.1128/aem.01018-09
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of a Cell Wall Protease in the Streptococcus thermophilus Population

Abstract: Streptococcus thermophilus is perceived as a recently emerged food bacterium that evolved from a commensal ancestor by loss and gain of functions. Here, we provide data allowing a better understanding of this evolutionary scheme. A multilocus sequence typing approach that we developed showed that S. thermophilus diverges significantly from its potential ancestors of the salivarius group and displays a low level of allelic variability, confirming its likely recent emergence. An analysis of the origin and dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
106
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 44 publications
(63 reference statements)
5
106
2
3
Order By: Relevance
“…The genome analysis showed that S. thermophilus UC8547 contains the prtS gene on the mobile genetic element previously identified in the fast-acidifying S. thermophilus strains. This genomic island is located in the ciaH-rpsT chromosomal region, as observed in other S. thermophilus strains (6,8), downstream of the ciaH pseudogene and between two tandem ISSth1 elements (Fig. 6).…”
Section: Resultssupporting
confidence: 57%
See 4 more Smart Citations
“…The genome analysis showed that S. thermophilus UC8547 contains the prtS gene on the mobile genetic element previously identified in the fast-acidifying S. thermophilus strains. This genomic island is located in the ciaH-rpsT chromosomal region, as observed in other S. thermophilus strains (6,8), downstream of the ciaH pseudogene and between two tandem ISSth1 elements (Fig. 6).…”
Section: Resultssupporting
confidence: 57%
“…Interestingly, proteolytic activity and biofilm formation are associated with the prtS gene, which is located on a mobile genetic element that has been demonstrated to be a horizontally acquired trait (6)(7)(8). The mechanism of prtS island excision involves two copies of the ISSth1 insertion sequence flanking the prtS gene and is similar to that already described by Delorme et al (8) in different S. thermophilus strains, and to that observed by Dandoy et al (6), inserting by natural transformation the island in PrtS Ϫ strains. Unlike other S. thermophilus prtS islands (8), in UC8547, there is a single copy of IS1167.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations